Correlation of sarcopenia with progression of liver fibrosis in patients with metabolic dysfunction-associated steatotic liver disease: a study from two cohorts in China and the United States - Fan Zhang; Longgen Liu; Wenjian Li (Nutrition Journal)
Abstract Objective The objective of this study was to investigate the association between sarcopenia and liver fibrosis in patients aged 18–59 years with metabolic dysfunction-associated steatotic liver disease (MASLD) and to assess the potential of sarcopenia as a risk factor for the progression of liver fibrosis. Methods The study included 821 patients with MASLD in the US cohort and 3,405 patients with MASLD in the Chinese cohort. Liver controlled attenuation parameters (CAP) and liver stiffness measurements (LSM) were assessed by vibration-controlled transient elastography (VCTE) to evaluate the extent of hepatic steatosis and fibrosis. Sarcopenia was assessed by measuring appendicular skeletal muscle mass (ASM) and calculating ASMI. To analyze the relationship between sarcopenia, ASMI, and liver fibrosis, logistic regression models, multivariate-adjusted models, and restricted cubic spline (RCS) models were employed, with stratification and interaction analyses. Results The results demonstrated that patients with sarcopenia exhibited a markedly elevated risk of significant liver fibrosis, advanced liver fibrosis, and cirrhosis compared to those without sarcopenia in both cohorts. After adjusting for confounding variables, sarcopenia was identified as an independent risk factor for the progression of liver fibrosis in patients with MASLD. A significant negative correlation was observed between ASMI and the severity of liver fibrosis, with a progressive reduction in the risk of liver fibrosis associated with increasing ASMI. Additionally, a non-linear feature was evident in some liver fibrosis indicators. Subgroup analysis further corroborated the finding that the harmful effect of sarcopenia on liver fibrosis was consistent across all identified subgroups. Conclusion Sarcopenia may be associated with the progression of liver fibrosis in patients with MASLD. Monitoring ASMI may assist in identifying individuals at an elevated risk of liver fibrosis in MASLD patients.